Profil Disiplin Belajar Peserta Didik Kelas VIII SMPN 4 Rancaekek Tahun Ajaran 2024/2025 - Danuansah, Asipa Cahya; Thahir, Muthahharah; Rachmaniar, Ananda (Jurnal Dimamu, 2025)
Learning discipline is one of the key factors that determine students’ academic achievement, particularly at the junior high school level. Students with high discipline tend to be more organized in managing their time, more focused on learning, and more consistent in completing academic tasks. This study aims to analyze the level of learning discipline among eighth-grade students at SMPN 4 Rancaekek in the 2024/2025 academic year, as well as to identify the factors influencing their discipline. The research employed a descriptive quantitative approach with a total population of 411 eighth-grade students, using a saturated sampling technique in which all students were included as respondents. The research instrument was developed based on several indicators of learning discipline, namely punctuality, compliance with academic rules, task completion, and positive academic behavior. The collected data were analyzed using descriptive statistical methods to portray the overall profile of students’ learning discipline. The findings reveal that most students fall into the moderate category across all aspects of learning discipline, while only a small proportion fall into the low category, and some achieve a high level of discipline. These results indicate that although a culture of discipline has been established at SMPN 4 Rancaekek, it has not yet reached an optimal level. Both external factors, such as family support and social environment, and internal factors, such as motivation and personal character, significantly influence the students’ discipline. Therefore, strengthening strategies through consistent habituation, the active role of teachers, parental involvement, and appropriate reinforcement are needed to enhance students’ discipline. This study is expected to provide valuable insights for schools in designing effective policies and programs to foster students’ learning discipline and to support their optimal academic achievement